2013
DOI: 10.1890/12-1165.1
|View full text |Cite
|
Sign up to set email alerts
|

Using citizen scientists to measure an ecosystem service nationwide

Abstract: The decomposition of dung constitutes an ecosystem service of massive proportions. Previous studies addressing how it depends on individual invertebrate taxa have been focused on small spatial scales, neglecting the impact of large-scale factors like climate. Here, we use the concept of "citizen science" to quantify taxon-specific contributions to dung decomposition at the level of a nation. Young people across Finland manipulated the decomposer communities of cow pats, then measured changes in pat mass over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 39 publications
(59 reference statements)
4
77
1
Order By: Relevance
“…Our lab experiment, as elsewhere [23], [33], [34], [35], showed that body mass is an ecologically relevant characteristic because smaller beetles had relatively little effect on dung removal. For example, the effect of O. fracticornis on dung removal was certainly lower compared to the other tunnelers used in the experiment and it was not significant after 80 hours (i.e.…”
Section: Discussionsupporting
confidence: 69%
“…Our lab experiment, as elsewhere [23], [33], [34], [35], showed that body mass is an ecologically relevant characteristic because smaller beetles had relatively little effect on dung removal. For example, the effect of O. fracticornis on dung removal was certainly lower compared to the other tunnelers used in the experiment and it was not significant after 80 hours (i.e.…”
Section: Discussionsupporting
confidence: 69%
“…Variation in nesting strategies [25] and in the body mass of species may significantly affect their functional efficiency [22,27,28,29,44]. Thus, we expected different beetles to affect GHG fluxes differently–a hypothesis for which we found direct support.…”
Section: Discussionmentioning
confidence: 62%
“…The ‘tunnelers’ translocate dung to tunnels dug underneath the dung pat, whereas the ‘rollers’ first translocate pieces of dung horizontally, then bury them vertically. A priori , these different nesting strategies and/or the body mass of the species may significantly affect ecological function, such as dung removal efficiency [22,2629]. As they result in inter alia holes of different diameter in different parts of the dung pat, and in different sizes of brood balls being translocated to different micro-environments, we hypothesized that they may also affect GHG fluxes differently.…”
Section: Introductionmentioning
confidence: 99%
“…We found that presence and biomass of tunnellers had a disproportionate effect on dung removal in a temperate wood‐pasture. This is in accordance with other experiments carried out in tropical and boreal habitats and shows the general importance of tunnellers for ecosystem functioning (Slade et al ., ; Kaartinen et al ., ). This is particularly the case for most Central European regions where roller species are absent and tunnellers are the most effective group from a functional perspective (Milotić et al ., ).…”
Section: Discussionmentioning
confidence: 97%